A core framework of “mountain management–water management–moist city” for sponge city special planning: The case of northwestern China - Wu, Ran; Yang, Ye; He, Junchao; Zhu, Jiang (Frontiers in Public Health, 2022)
Sponge city special planning represents a basis for sponge city construction in China. It has a leading role in problem-oriented, effect-centered comprehensive, and coordinated construction. In accordance with the Interim Provisions on the Formulation of Sponge City Special Planning, China has gradually established a standardized method for formulating sponge city special planning based on the “four-water” framework. While this method emphasizes the normalization of planning contents, it has limitations when dealing with regional characteristics. The present paper clarifies the purposes and demands of formulating sponge city special planning for semi-arid valley cities in northwestern China. It furthermore highlights the limitations of the standard method and suggests a three-level optimization, i.e., problem identification, target indicators, and system construction. Based on the framework of “mountain management–water management–moist city,” this paper proposes a set of ideas for formulating sponge city special planning. In this regard, the discussions are based on the formulation practice of Xining.